Hybrid double-spiral microfluidic chip for RBC-lysis-free enrichment of rare cells from whole blood. Issue 22 (28th October 2022) - Shirai, Kentaro; Guan, Guofeng; Meihui, Tan; Xiaoling, Peng; Oka, Yuma; Takahashi, Yusuke; Bhagat, Ali Asgar S.; Yanagida, Masatoshi; Iwanaga, Shigeki; Matsubara, Nobuaki; Mukohara, Toru; Yoshida, Tomokazu
Abstract : Hybrid double-spiral chip was developed to enrich circulating tumor cells (CTCs) without red blood cell lysis for liquid biopsy. Combined with the imaging flow cytometry, CTCs detection from cancer patient blood was demonstrated. Abstract : Drug selection and treatment monitoring via minimally invasive liquid biopsy using circulating tumor cells (CTCs) are expected to be realized in the near future. For clinical applications of CTCs, simple, high-throughput, single-step CTC isolation from whole blood without red blood cell (RBC) lysis and centrifugation remains a crucial challenge. In this study, we developed a novel cancer cell separation chip, "hybrid double-spiral chip", that involves the serial combination of two different Dean flow fractionation (DFF) separation modes of half and full Dean cycles, which is the hybrid DFF separation mode for ultra-high-throughput blood processing at high precision and size-resolution separation. The chip allows fast processing of 5 mL whole blood within 30 min without RBC lysis and centrifugation. RBC and white blood cell (WBC) depletion rates of over 99.9% and 99%, respectively, were achieved. The average recovery rate of spiked A549 cancer cells was 87% with as low as 200 cells in 5 mL blood. The device can achieve serial reduction in the number of cells from approximately 10 10 cells of whole blood to 10 8 cells, and subsequently to an order of 10 6 cells. The developed method can be combined with measurements of all recovered cells using imaging flow cytometry. As proof of concept, CTCs were successfully enriched and enumerated from the blood of metastatic breast cancer patients ( N = 10, 1–69 CTCs per 5 mL) and metastatic prostate cancer patients ( N = 10, 1–39 CTCs per 5 mL). We believe that the developed method will be beneficial for automated clinical analysis of rare CTCs from whole blood.